MISI PENGGABUNGAN TIGA BANK SYARIAH PEMERINTAH TERHADAP LOYALITAS NASABAH TANTANGAN GLOBALISASI - Rustomo, Rustomo (Universitas Nusa Cendana, 2024)
The objective of the merger of the three Islamic banks is to strengthen the national banking industry's performance and solidify effective and efficient financing. Guarantees to customers to remain loyal in choosing Bank Syariah Indonesia are the projections and achievements of Bank Syariah Indonesia institutions. The research was compiled using a quantitative description method with all respondents of Bank Syariah Indonesia KCP Karawang customers with primary data distributing questionnaires with Likert five scales where respondents expressed their opinions. The results of the data analysis show that the average respondent has been a customer for two years. The merger at Bank Syariah Indonesia on customer loyalty is significant and has linearity and good normality. The level of relationship between the two independent and dependent variables is stated to be low but has a positive trend that is always changing. Keywords: Bank Merger; Customer Loyalty; Globalization